2018
DOI: 10.1002/jsfa.8915
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Aloe vera gel incorporation on the physicochemical and mechanical properties of banana starch‐chitosan edible films

Abstract: Our results suggest that the addition of AV gel creates a crosslinking effect between the phenolic compounds in AV gel and starch molecules, which disrupts the starch-chitosan interaction and greatly affects the properties of both the film-forming solution and edible films. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 50 publications
(70 reference statements)
11
35
0
2
Order By: Relevance
“…Enhancement of glycerol and Aloe vera concentration produce transmission of water vapor become lower. In accordance to the Pinzon et al, (2018) the presence of Aloe vera reduced the hydrophilic groups availability in starch and decreased the WVTR by a crosslinking effect with the starch molecules. The height of water vapor transmission rate indicates the component that can pass through the edible film also greater.…”
Section: Wvtr Of Edible Filmsupporting
confidence: 58%
“…Enhancement of glycerol and Aloe vera concentration produce transmission of water vapor become lower. In accordance to the Pinzon et al, (2018) the presence of Aloe vera reduced the hydrophilic groups availability in starch and decreased the WVTR by a crosslinking effect with the starch molecules. The height of water vapor transmission rate indicates the component that can pass through the edible film also greater.…”
Section: Wvtr Of Edible Filmsupporting
confidence: 58%
“…It has been reported that the porosity of the fruit surface might be reduced due to the binding of AV molecules to the fruit surface (Song, Jo, Song, Min, & Song, 2013). Previous studies have shown that different components of AV gel (polysaccharides such as pectins, hemicelluloses, glucomannan, acemannan, and mannose derivatives, lipids, and tannins) can suppress its water vapor permeability and reduce water loss when applied to strawberry fruit (Ergun & Satici, 2012; Marpudi, Abirami, Pushkala, & Srividya, 2011; Martínez‐Romero et al., 2006; Pinzon, Garcia, & Villa, 2018; Valverde et al., 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The thickness of this research is higher than Arifin et al (2016) that studied the 0.1% and 0.5% glycerol in Aloe Gel edible film produce thickness 0.076 and 0.089 mm, respectively. Other research showed that the thickness of edible film with addition of Aloe Vera gel 300 ml, 30g/l banana starch, chitosan 20 g/L and sorbitol 10 g/L amounted to 0.135 mm (Pinzon, 2018).…”
Section: Thickness Of Edible Filmmentioning
confidence: 97%